Akbar (1556-1605) and India unification under the mughals - Jamsari E.A.; Hassan Ashari M.Z.A.; Nor M.R.M.; Sulaiman A.; Safiai M.H.; Ibrahim I.A.; Ahmad M.Y. (IAEME Publication, 2024)
Indexed by Scopus